COMPUTATIONAL ANALYSIS OF FLOW CHARACTERISTICS AROUND A TWIN-SPLINED CYLINDER WITHIN A 2-D CHANNEL - Chamoli, Sunil; Sahi, Samarth; Jaiswal, Shivam; Negi, Anant; Pant, Pawan Kumar; Joshi, Amit; Eiamsa-Ard, Smith; Thianpong, Chinaruk (My University, 2024)
In the present research work, external flow-induced stresses on a circular cylinder with double-splined surfaces are investigated at a Reynolds number Re of 100. Opposite sides of the cylinder have splined surfaces. The splines are positioned between 0° and 90° from the cylinder's front and rear stagnation points. It is demonstrated that the spline on the cylinder's leading edge modifies the vortex dynamics and causes considerable changes in flow-induced forces. At Re = 100, when a spline is placed on a cylinder's surface, noticeable reduction is observed in the coefficients of lift and drag compared to a smooth cylinder. When the inclination angle is increased to a maximum of 60°, the stagnation point moves to the windward side. Additionally, the spline in the front and back side of the cylinder significantly strengthens the vortex flow. At inclinations of 90° and 0°, maximal and minimal vorticities are obtained. Furthermore, the present work's double-spline cylinder demonstrates the advantage of reduced drag over many previously reported bluff bodies.
Keywords: double spline; drag coefficient; inclination; lift coefficient; numerical simulation; vortex shedding; vorticity